The Effect of Preoperative Symptom Duration on Patient-Reported Outcomes After Anterior Cervical Discectomy and Fusion in Nonmyelopathic Patients: Analyses From the Michigan Spine Surgery Improvement Collaborative (MSSIC). Issue 5 (16th May 2023) - Lawless, Michael H.; Tong, Doris; Claus, Chad F.; Hanson, Connor; Li, Chenxi; Park, Paul; Chang, Victor W.; Abdulhak, Muwaffak M.; Houseman, Clifford M.; Bono, Peter L.; Carr, Daniel A.; Richards, Boyd F.; et al.
Abstract : BACKGROUND: The effect of preoperative symptom duration (PSD) on patient-reported outcomes (PROs) in anterior cervical discectomy and fusion (ACDF) for radiculopathy is unclear. OBJECTIVE: To determine whether PSD is a predictor for PRO after ACDF for radiculopathy. METHODS: The Michigan Spine Surgery Improvement Collaborative registry was queried between March, 2014, and July, 2019, for patients who underwent ACDF without myelopathy and PROs (baseline, 90 days, 1 year, 2 years). PROs were measured by numerical rating scales for neck/arm pain, Patient-Reported Outcomes Measurement Information System Short Form-Physical Function (PROMIS-PF), EuroQol-5D (EQ5D), and North American Spine Society satisfaction. Univariate analyses were used to evaluate the proportion of patients reaching minimal clinically important differences (MCID). PSD was <3 months, 3 month-1 year, or >1 years. Multiple logistic regression models were used to estimate the association between PSD and PRO reaching MCID. The discriminative ability of the model was evaluated by receiver operating characteristic curve. RESULTS: We included 2233 patients who underwent ACDF with PSD <3 months (278, 12.4%), 3 month-1 year (669, 30%), and >1 years (1286, 57.6%). Univariate analyses demonstrated a greater proportion of patients achieving MCID in <3-month cohort for arm numerical rating scales, PROMIS-PF, EQ5D, and North American Spine Society Satisfaction. Multivariable analyses demonstrated using <3 months PSD as a reference, PSD >1 years was associated with decreased odds of achieving MCID for EQ5D (odds ratio 0.5, CI 0.32-0.80, P = .004). Private insurance and increased baseline PRO were associated with significantly higher odds for achieving PROMIS-PF MCID and EQ5D-MCID. CONCLUSION: Preoperative symptom duration greater than 1 year in patients who underwent ACDF for radiculopathy was associated with worse odds of achieving MCID for multiple PROs.